"A Time of Opportunity": Patient Safety and the Perioperative Surgical Home. (December 2016) - Garson, Leslie M.; Vakharia, Shermeen; Edwards, Angela F.; Maze, Mervyn
Abstract : Published ahead of print September 16, 2016.